The European Stroke Organisation Guidelines: a standard operating procedure. (6th July 2015) - Ntaios, George; Bornstein, Natan M.; Caso, Valeria; Christensen, Hanne; De Keyser, Jacques; Diener, Hans‐Christoph; Diez‐Tejedor, Exuperio; Ferro, Jose M.; Ford, Gary A.; Grau, Armin; Keller, Emanuella; Leys, Didier; et al.
Abstract : In 2008, the recently founded European Stroke Organisation published its guidelines for the management of ischemic stroke and transient ischemic attack. This highly cited document was translated in several languages and was updated in 2009. Since then, the European Stroke Organisation has published guidelines for the management of intracranial aneurysms and subarachnoidal hemorrhage, for the establishment of stroke units and stroke centers, and recently for the management of intracerebral hemorrhage. In recent years, the methodology for the development of guidelines has evolved significantly. To keep pace with this progress and driven by the strong determination of the European Stroke Organisation to further promote stroke management, education, and research, the European Stroke Organisation decided to delineate a detailed standard operating procedure for its guidelines. There are two important cornerstones in this standard operating procedure: The first is the implementation of the Grading of Recommendations Assessment, Development, and Evaluation methodology for the development of its Guideline Documents. The second one is the decision of the European Stroke Organisation to move from the classical model of a single Guideline Document about a major topic (e.g. management of ischemic stroke) to focused modules (i.e. subdivisions of a major topic). This will enable the European Stroke Organisation to react faster when new developments in a specific stroke field occur and update its recommendations on the related module rather swiftly; with the previous approach of a single large Guideline Document, its entire revision had to be completed before an updated publication, delaying the production of up‐to‐date guidelines. After discussion within the European Stroke Organisation Guidelines Committee and significant input from European Stroke Organisation members as well as methodologists and analysts, this document presents the official standard operating procedure for the development of the Guideline Documents of the European Stroke Organisation.